2017
DOI: 10.1002/ejic.201700910
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Influence on the Photophysical Properties and Electronic Structures of Tungsten Iodide Clusters

Abstract: Compounds containing the [Mo6I8L6]2– ion in which L is an inorganic or organic ligand show remarkable photophysical properties. Similar properties were observed for the corresponding compounds based on octahedral tungsten clusters. The properties of these photosensitizers are significantly impacted by the six outer iodide ligands of [W6I8I6]2–. To analyze the role of the outer ligands, we prepared and structurally characterized octahedral tungsten cluster compounds with [W6I8I6]2– and [M6I8L6]2– ions (M = W, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
(69 reference statements)
1
21
0
Order By: Relevance
“…( n Bu 4 N) 2 [W 6 I 14 ] and other compounds based on the [W 6 I 14 ] 2– clusters represent prominent materials for optical properties (luminescence, singlet oxygen production) , . Alkali compounds A 2 [W 6 I 14 ] have shown poor luminescence properties in solid state, due to their dark body colors , .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…( n Bu 4 N) 2 [W 6 I 14 ] and other compounds based on the [W 6 I 14 ] 2– clusters represent prominent materials for optical properties (luminescence, singlet oxygen production) , . Alkali compounds A 2 [W 6 I 14 ] have shown poor luminescence properties in solid state, due to their dark body colors , .…”
Section: Resultsmentioning
confidence: 99%
“…Compounds were used as purchased without any further purification: WCl 6 (Acros Organic, 99.9+ %), SiI 4 [20] The reaction of 50 mg (0.013 mmol) W 6 I 22 and (AE)I (50 mmol) was carried out in acetone solution (50 mL) under air. After one day of stirring, the product can be obtained as a precipitated dark Z. Anorg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds show strong long‐lived luminescence and significant quenching by O 2 in the solid state and in solution. The electronic structures reveal decrease in the HOMO and LUMO energy levels following the order [W 6 I 14 ] 2– > [{W 6 I 8 }(OTs) 6 ] 2– > [{Mo 6 I 8 }(OTs) 6 ] 2– , , . The lability of tosylate in (Bu 4 N) 2 [{M 6 I 8 }(OTs) 6 ] is such that it can be substituted with solvent molecules (100° C, 14.5 h, with the formation of [M 6 I 8 (pts) 6‐x (CH 3 CN) x ] –(2–x) (x = 1–2) and [M 6 I 8 (pts) 6‐x ((CD 3 ) 2 SO) x ] –(2–x) (x = 4–6), respectively.…”
Section: Octahedral Clusters: Chemistrymentioning
confidence: 99%
“…Photoluminescence studies on crystalline (TBA) 2 [W 6 I 14 ] (TBA = tetrabutylammonium) have shown the absence of a significant phosphorescence quenching, revealing the absence of an energy transfer from the iodide cluster onto atmospheric O 2 in solid state . The same behavior is evidenced for M = Mo .…”
Section: Introductionmentioning
confidence: 77%